2007
DOI: 10.1016/j.ahj.2007.02.011
|View full text |Cite
|
Sign up to set email alerts
|

Long-term survival after successful inhospital cardiac arrest resuscitation

Abstract: Background-Little is known about long-term outcomes of patients who survive inhospital cardiac arrest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
56
4

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 35 publications
1
56
4
Order By: Relevance
“…It was reported that ventricular tachycardia/ventricular fibrillation was independently associated with survival to hospital discharge in patients with in-hospital and out-of-hospital CA. 16 In the present study, however, the first documented rhythm was not associated with survival. This might have been due to the relatively small number of patients (n=50, 47.6%) with out-of-hospital CA in the present study.…”
Section: Other Potential Factors Predicting Survival After Pcpscontrasting
confidence: 72%
See 1 more Smart Citation
“…It was reported that ventricular tachycardia/ventricular fibrillation was independently associated with survival to hospital discharge in patients with in-hospital and out-of-hospital CA. 16 In the present study, however, the first documented rhythm was not associated with survival. This might have been due to the relatively small number of patients (n=50, 47.6%) with out-of-hospital CA in the present study.…”
Section: Other Potential Factors Predicting Survival After Pcpscontrasting
confidence: 72%
“…The overall survival rate of patients who experienced in-hospital CA, however, remains unsatisfactory. 16 It was reported that cardiopulmonary resuscitation (CPR) assisted with ACLS improved the survival rate of in-hospital CA patients. 7, 15 Based on the present findings, we recommend that immediate PCPS should be considered when in-hospital CA patients with cardiovascular disease do not response to ACLS.…”
Section: Other Potential Factors Predicting Survival After Pcpsmentioning
confidence: 99%
“…21 The GOS-E provides a global measure of function on an 8-level scale from death (1) to upper good recovery (8) and can be administered by proxy or direct interview with the patient. Domains such as self-care, mobility, return to work, relationship, and social and leisure activities are considered.…”
Section: Outcome Measuresmentioning
confidence: 99%
“…6 Despite this finding, there are concerns that many survivors are substantially disabled with poor long-term quality of life. 7,8 Given that there is significant investment in improving the emergency response to OHCA patients 9,10 and reported improvements in short-term survival outcomes, the long-term neurological state and quality of life of survivors is of growing significance.…”
mentioning
confidence: 99%
“…While cardiopulmonary resuscitation for victims of cardiac arrest succeeds in restoring spontaneous circulation in about 70,000 patients per year in the US 7,8 at least 60% of these patients subsequently die in the hospital as a result of extensive brain damage and only 3-10% of resuscitated patients can resume their former lifestyles 9,10 . Clearly, understanding the mechanisms that lead to brain damage following global brain ischemia and designing therapeutic interventions to minimize neurologic trauma is of critical importance.…”
Section: Introductionmentioning
confidence: 99%